Resilience and Subjectively Experienced Stress Among Paramedics Prior to and During the COVID-19 Pandemic - Piotrowski, Andrzej; Makarowski, Ryszard; Predoiu, Radu; Predoiu, Alexandra; Boe, Ole (Frontiers in Psychology, 2021)
Introduction. Paramedics play a vital role in the healthcare system by providing professional support in situations of direct threat to patient health and life. They experience numerous difficulties during their work, which result in occupational stress. During the COVID-19 pandemic, their work has become even more demanding. The aim of the current study was to examine the role of resilience in the subjective experience of stress among paramedics during the COVID-19 pandemic. Materials and methods. The study was carried out in two phases, in October-November 2019 (N = 75) and in May-June 2020 (N = 84), using the Sense of Stress Questionnaire (Skala Poczucia Stresu) and the Resilience Scale (Skala Pomiaru Prężności). Results. Paramedics exhibited higher intrapsychic stress before the COVID-19 pandemic. Tolerance of failure and treating life as a challenge were higher during the pandemic, in contrast to optimism and the ability to mobilize in difficult situations. Paramedics who were in contact with patients with COVID-19 experienced higher stress. Perseverance and determination, openness to new experiences and sense of humor, as well as competences and tolerance of negative emotions were revealed to play a key part in mitigating subjectively experienced stress. Conclusions. Paramedics’ subjectively experienced stress was lower during the COVID-19 pandemic. Paramedics who were in direct contact with patients with COVID-19 experienced higher stress. They had sufficient psychological resources, in the form of resilience (perseverance and determination, openness to new experiences, sense of humor, and competences and tolerance of negative emotions), which allowed them to cope with the situation of the COVID-19 pandemic.